MiR-6315 silencing protects against spinal cord injury through the Smo and anti-ferroptosis pathway. Issue 4 (6th April 2023) - Ma, Zheng; Fan, Yan; Peng, Yufang; Bian, Ligong; Zhou, Jianping; Wang, Lijuan; Xia, Yan; Zheng, Sili; Ji, Yanlian; Han, Yanbing; Feng, Chengan; Ba, Yingchun
Abstract: Spinal cord injury (SCI) causes permanent damage and has a high disability rate. Currently, no efficient therapeutic strategy is available for SCI. The present study investigated the mechanisms of microRNAs (miRNAs) in rats with spinal cord injury. Whole transcriptome sequencing (WTS) was used for analyzing miRNA and messenger RNA (mRNA) expression patterns in rat spinal cord tissue at different time points after SCI. Gene Ontology (GO) and KEGG pathways were analyzed to obtain crucial functional pathways. miR-6315 was the most significantly up-regulated and differentially expressed miRNA after 24 h of SCI; the expression of miR-6315 gradually decreased after 3 and 7 days of SCI. Bioinformatics analysis was conducted to predict the targeting relation of miR-6315 with Smo, and qRT-PCR and dual-luciferase reporter assays were conducted for verification. The miR-6315 silencing (miR-6315-si) adenovirus was successfully constructed. miR-6315 knockdown treatment significantly promoted functional behavioral recovery in rats post-SCI through using Basso–Beattie–Bresnahan (BBB) locomotor rating scale and the inclined plane test. The neuronal axon regeneration and neuronal migration were promoted, and cell apoptosis was attenuated in treated SCI rats and Glu-treated neurons after miR-6315 knockdown using immunofluorescence and scratch assays. We discovered that Smo and anti-ferroptosis pathway factors, xCT, GSH, and GPX4, may be involved in miR-6315-regulated SCI repair. The expression of miR-6315 was negatively correlated with Smo, xCT, GSH, and GPX4. In conclusion, miR-6315 may be a potential target in the treatment of SCI.